Cold asphalt mix with emulsion and 100% rap: Compaction energy and influence of emulsion and cement content. (30th July 2020) - Flores, Guillermo; Gallego, Juan; Miranda, Lucía; Marcobal, José Ramón
Graphical abstract: Highlights: The RAP from the field is used without the addition of virgin aggregate for cold recycling mixture. The percentage of the emulsion is the factor that most affects the compactability of the mixture. The emulsion improves tensile strength and, resistance to water attack but worsens plastic deformation. The cement enhances the ITSR, resistance to rutting, stiffness modulus and fatigue resistance. Abstract: The present work aims at determining the conditions for the compaction of cold recycled mixtures with emulsion and 100% RAP. Additionally, the influence of the emulsion and cement on the final properties of the recycled mixtures has been investigated. To achieve these purposes, reclaimed asphalt material coming from the milling of a distressed pavement was mixed with different proportions of water, asphalt emulsion and cement. The mixtures were compacted by a gyratory compactor. As a result of the investigation, it is recommended to apply a compaction energy level of 100 gyrations for specimens 100 mm diameter and 60 mm height, and an energy of 200 gyrations for specimens 100 mm diameter and 100 mm height. As for the mechanical properties of the mixtures, the laboratory tests showed that the presence of cement contributes to improving the sensitivity to water attack, the resistance to permanent deformations, the stiffness modulus and the fatigue life of the mixtures.